2022
DOI: 10.3390/nano12193265
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Spinosum Capacitive Pressure Sensor Based on CNT/PDMS Nanocomposites for Broad Range and High Sensitivity

Abstract: Flexible pressure sensors have garnered much attention recently owing to their prospective applications in fields such as structural health monitoring. Capacitive pressure sensors have been extensively researched due to their exceptional features, such as a simple structure, strong repeatability, minimal loss and temperature independence. Inspired by the skin epidermis, we report a high-sensitivity flexible capacitive pressure sensor with a broad detection range comprising a bioinspired spinosum dielectric lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The results show that LPV-5 presents stable responses with excellent repeatability. Figure d shows a high sensitivity response over a wide response range compared to reported pressure sensors, demonstrating the supereminent sensing properties of our LPV-5 sensor. …”
Section: Resultsmentioning
confidence: 68%
“…The results show that LPV-5 presents stable responses with excellent repeatability. Figure d shows a high sensitivity response over a wide response range compared to reported pressure sensors, demonstrating the supereminent sensing properties of our LPV-5 sensor. …”
Section: Resultsmentioning
confidence: 68%
“…The high sensitivity along with the fast response may benefit from the face-to-face placement of the two different micro buckling structures. The sensitivity and response are superior to those of the newly reported vertical graphene/micropyramidal PDMS piezocapacitive pressure sensor, the reported capacitive sensor using a porous micropillar PDMS as the dielectric layer (∼20 ms), and the spinosum capacitive pressure sensor based on CNT/PDMS nanocomposites (∼20 ms) . The high sensitivity can be attributed to the micro pyramid structure of the dielectric layer and the air gap between the wrinkle structure and the pyramid structure.…”
Section: Resultsmentioning
confidence: 70%
“…The sensitivity and response are superior to those of the newly reported vertical graphene/micropyramidal PDMS piezocapacitive pressure sensor, 34 the reported capacitive sensor using a porous micropillar PDMS as the dielectric layer (∼20 ms), 44 and the spinosum capacitive pressure sensor based on CNT/ PDMS nanocomposites (∼20 ms). 45 The high sensitivity can be attributed to the micro pyramid structure of the dielectric layer and the air gap between the wrinkle structure and the pyramid structure. The micro pyramid produced using the buckling method may be more compressible than the similar patterns generated by other methods.…”
Section: Performance Of the Piezocapacitive Sensor The Piezocapacitiv...mentioning
confidence: 99%
“…To achieve a high sensitivity over a wide range, Δε/ε r0 is another key parameter. Notably, studies have shown that adding a conducting filler to the polymer can result in large dielectric permittivity. Here, MWCNTs are added to the high- E component of the GD to form the GHD. Figure e shows the Δ C / C 0 of the sensors based on the bulk dielectric (BD), GD, and GHD under different applied pressures.…”
Section: Resultsmentioning
confidence: 99%